THE IMPACT OF COVID-19 LOCKDOWN ON PET DOG MANAGEMENT IN SERBIA - Rakita, Slađana; Vujetić, Jelena; Stojkov, Viktor; Vasić, Milica; Vidosavljević, Strahinja; Kokić, Bojana; Đuragić, Olivera (Food and Feed Research, 2024)
On March 15, 2020, the Serbian government introduced a nationwide lockdown to prevent the spread of COVID-19. The enforcement of lockdown measures led to changes in the daily lives of dog owners, which, in turn, affected the routines of their dogs. Therefore, this study aimed to investigate the effects of Serbian lockdown measures enforced for the control of the COVID-19 pandemic on pet dog management. Therefore, we conducted an online questionnaire survey with Serbian dog owners in the period from July 15 to August 31, 2021. A total of 384 pet owners older than 18 years participated. The survey comprised 34 questions about owners’ demographic information, information about their dogs, changes in dog walking and feeding practices, as well as behavior before and after the COVID-19 lockdown. The results indicated that there was no notable rise in the rate of dog adoption or purchase. Furthermore, we found that dog owners decreased the frequency of walks for their pets in nature or walking fields, choosing instead to keep them indoors or confine them to the backyard more frequently. Some owners believed that their dogs became slightly passive or nervous as a response to enforced lockdown restrictions. No significant changes in dog feeding practices were reported, although a minority of dog owners noted that their dogs consumed slightly less food during the lockdown but gained a small amount of weight. Additionally, owners reported no pronounced changes in the amount of money they spent on dog food. The data collected provide substantial insight into how dogs’ quality of life and routine as well as dog-owner interaction were affected by the COVID-19 lockdown.